The revenant eaudiobook - Punke, Michael (Macmillan Audio, 2015)
NOW A MAJOR MOTION PICTURE #1 NEW YORK TIMES BESTSELLER A thrilling tale of betrayal and revenge set against the nineteenth-century American frontier, Michael Punke's The Revenant is the astonishing story of real-life trapper and frontiersman Hugh Glass The year is 1823, and the trappers of the Rocky Mountain Fur Company live a brutal frontier life. Hugh Glass is among the company's finest men, an experienced frontiersman and an expert tracker. But when a scouting mission puts him face-to-face with a grizzly bear, he is viciously mauled and not expected to survive. Two company men are dispatched to stay behind and tend to Glass before he dies. When the men abandon him instead, Glass is driven to survive by one desire: revenge. With shocking grit and determination, Glass sets out, crawling at first, across hundreds of miles of uncharted American frontier. Based on a true story, The Revenant is a remarkable tale of obsession, the human will stretched to its limits, and the lengths that one man will go to for retribution.